Probiotic aplication for growth and survival rate of vaname shrimp Litopenaeus vannamei with different density - Abdul Rakhfid; Wa Ode Halida; Rochmady Rochmady; Fendi Fendi (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
The study aimed to determine the growth and survival of Litopenaeus vannamei shrimp with the application of probiotics to different stocking densities. The study was conducted from May to June 2018 at the Balai Benih Ikan Pantai (BBIP) Ghonebalano, Duruka District, Muna Regency, using a Completely Randomized Design (CRD) with three levels of solid stocking treatment namely treatment A is 18 individu per container, treatment B is 24 individu per container and treatment C is 30 individu per container with three replications. Data analysis using Variance Analysis (ANOVA) at the confidence level of 95% (α 0.05). The results showed that the highest daily growth was obtained at 24 individual densities of 5.88% per day, compared to 18 individual densities of 5.86% per day and 30 individual densities of 5.74% per day. The highest absolute growth is obtained at 24 individual density of 2.43 g per individu, then 18 individual density of 2.15 g per individual, and the lowest at 30 individual density of 2.02 g per individual. Survival at a density of 18 individual and a density of 24 individual at 88.89%, while a 30-ind density of 86.67%. Analysis of variance (α 0.05) showed that the application of probiotics to different stocking densities had no significant effect on the daily growth rate of vannamei shrimp (p<0.939), absolute growth of vannamei shrimp (p<0.080), and survival of vannamei shrimp (p<0.744).